'Climate change mitigation is a hot topic, but not when it comes to hospitals': a qualitative study on hospital stakeholders' perception and sense of responsibility for greenhouse gas emissions. Issue 3 (22nd April 2022) - Quitmann, Claudia; Sauerborn, Rainer; Danquah, Ina; Herrmann, Alina
Abstract : Objective: Physical and mental well-being are threatened by climate change. Since hospitals in high-income countries contribute significantly to climate change through their greenhouse gas (GHG) emissions, the medical ethics imperative of 'do no harm' imposes a responsibility on hospitals to decarbonise. We investigated hospital stakeholders' perceptions of hospitals' GHG emissions sources and the sense of responsibility for reducing GHG emissions in a hospital. Methods: We conducted 29 semistructured qualitative expert interviews at one of Germany's largest hospitals, Heidelberg University Hospital. Five patients, 12 clinical and 12 administrative employees on different levels were selected using purposive maximum variation sampling. Interviews were transcribed verbatim and analysed using the framework approach. Results: Concerning GHG emissions, hospital stakeholders perceived energy and waste as most relevant emission sources followed by mobility. Climate change mitigation in general was considered as important. However, in their role as patients or employees, hospital stakeholders felt less responsible for climate change mitigation. They saw providing best possible medical care to be the top priority in hospitals and were often concerned that patients' health could be jeopardised by climate change mitigation measures. Conclusion: Perceptions of most important emission sources did not coincide with those in literature, highlighting the need to inform stakeholders, for instance, about pharmaceuticals as important emission source. A frequently perceived conflict between reducing emissions and providing high-quality medical care could be eased, if reducing emissions would not only be justified as a contribution to mitigation, but also as a contribution to preventing ill health—a basic principle of medical ethics.